Oszustwo szkodowe i bezszkodowe jako dwie odmiany przestępstwa oszustwa - Bielski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This study contains a juridical analysis that presents the grounds for establishing differentiation with respect to the fraud offense regulated in Article 286 § 1 of the Criminal Code. The fraud offense may be divided into two distinctive types — fraud causing damages that results in suffering substantial material damages by an injured party, and so-called no-damage fraud that is limited in its effect to creating a state of exposure to direct danger of financial interest of an injured party. The article includes the analysis of substantive and procedural consequences of differences that arise between those two specified types of the fraud offense.
Keywords: przestępstwo oszustwa; oszustwo; Art. 286 § 1 Kodeksu karnego; znaczne szkody materialne